Geo-Information Modeling of Soil Erosion for Sustainable Agriculture Land Management in Sambhunath Municipality - Karna, Bikash Karma; Shrestha, Shobha; Koirala, Hriday Lal (Journal on Geoinformatics, Nepal, 2020)
Geo-information science has attempted to estimate the actual soil loss and its correlative interpretation with land use and cover types in an agricultural land, Sambhunath Municipality. Among several empirical and physically based soil erosion models, Revised Universal Soil Loss Equation (RUSLE) are widely used and employed to estimate soil loss based on rainfall, topographic contour, and soil map. The soil erosion ranges values are found from 0 to 2635 t ha-1 yr-1 in terms of soil loss per year in the municipality. Soil erosion rates are found highly correlated with the increasing exposure of land surface in Chure range mostly on forest area. Agriculture lands spatially concentrated in 51.70% of the Municipality extent, is contributing significantly as of 16293 t ha-1 yr-1 of the total potential soil loss from fertile cropland. Based on severity of soil loss, cultivation agriculture areas are priority for reducing soil loss for optimum agriculture management practices in land use planning.